Yield surface curvature and the stability of a cruciform column. (5th December 2022) - Scherzinger, W.M.
Abstract: Many isotropic and anisotropic yield surface definitions have been developed and published in the literature. These models allow a greater flexibility to simulate yield in pure shear, anisotropic yield, anisotropic flow, and tension/compression asymmetry. With the increase in simulation fidelity provided by these models, it is useful to study the proposed yield surfaces in greater detail to gain a better understanding of how different features of the surfaces manifest themselves in boundary value problems. One feature which has a significant effect on the behavior of structures is the curvature of the yield surface. In this work, yield surface curvature is quantified and applied to the instability of a cruciform column in compression. Results show that the curvature of the yield surface has a strong effect on stability of the column.